Building a Maritime Generation : An Analysis of Students' Perceptions of Maritime-Based Learning at Maritime Raja Ali Haji University - -, Alifya Rahma Aillah; -, Ferdian Ramadhana; -, Mirza Ayunda Pratiwi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Maritime Raja Ali Haji University, as the only maritime university in Indonesia and a benchmark for maritime-based campuses, has an important role in improving maritime insights. This study aims to analyze the perception of students of the Faculty of Maritime Economics and Business towards the implementation of maritime-based learning at Maritime Raja Ali Haji University. Student perception and the effectiveness of maritime-based learning are the main focus in this study. This study uses a qualitative method with a descriptive approach, where data is collected through in-depth interviews and observations of students who have taken several maritime-based courses. The research informants consisted of 15 students from the 2022 and 2023 batches who were selected by purposive sampling based on their active involvement in academic and non-academic activities related to the maritime sector. The results of the study show that most students have a varied perception of the integrity and relevance of maritime-based courses. However, there are several obstacles such as limited supporting facilities and variations in teaching methods that are considered less interactive. This study concludes that students of the Faculty of Maritime Economics and Business have great potential to become a superior maritime generation. However, there needs to be a more comprehensive effort from various parties to improve the quality of maritime-based learning. This can be done by strengthening cooperation between universities, industry, and the government, as well as actively involving students in the process of developing curriculum and maritime-based learning activities.